Consideration of Tourism Riverfront Development Elements for Pekanbaru City Transformation - Fithria Khairina Damanik; Wiwik Dwi Pratiwi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Abstract. Pekanbaru is the capital of Riau which is well known as a business city with a strategic location between the trade routes of Sumatera. The city obviously has Siak River as its tourism potential. However, the river, which is one of the deepest and longest rivers in Indonesia, lately is no longer be the face of the city and is not managed optimally. This study can support the reviving of the river through riverfront tourism development. This study will discuss the consideration of development elements of riverfront tourism for Siak River, focusing on the urban villages of Kampung Bandar and Kampung Dalam, Senapelan Sub-district as the study location. The elements consist of function, image, theme, geographic factor, authenticity, accessibility, community perception and management which is based on a modification of the theories of Toree (1989) and Wren (1983). This study uses a mixed method approach, using a quantitative approach for community and visitors perception about the location and a qualitative approach for the analysis of riverfront tourism development elements. The data is collected through questionnaires, field observation, and interviews with relevant stakeholders. Based on the analysis, the study location already has the elements to form a riverfront tourism area and has the potential to be developed as the riverfront icon of Pekanbaru, yet it still needs strategies for improvement to build a new destination. The recommendations of destination development strategies consist of attraction development, facility development, accessibility development, and community empowerment through tourism, and also additional development strategies consisting of promotion and tourism organization development. Keywords: development elements, tourism, riverfront, Siak River.Abstrak. Kota Pekanbaru merupakan ibukota Provinsi Riau yang dikenal sebagai kota bisnis dengan lokasi strategis di antara jalur perdagangan Sumatera, nyatanya memiliki potensi pariwisata berupa Sungai Siak. Namun, Sungai Siak yang merupakan salah satu sungai terdalam dan terpanjang di Indonesia serta membelah Kota Pekanbaru menjadi dua bagian ini, nyatanya mulai berkembang menjadi tampak belakang kota dan tidak dikelola secara maksimal. Artikel ini menjadi salah satu studi yang dapat mendukung penghidupan kembali fungsi sungai melalui pengembangan pariwisata di pinggir sungai (riverfront). Artikel ini akan membahas konsiderasi elemen pengembangan kawasan pariwisata riverfront Sungai Siak dengan fokus lokasi di Kelurahan Kampung Bandar dan Kampung Dalam Kecamatan Senapelan. Elemen pengembangan kawasan riverfront yang terdiri dari fungsi, citra, tema, faktor geografis, autentisitas, aksesibilitas, persepsi, dan manajemen berdasarkan modifikasi teori oleh Toree (1989) dan Wren (1983). Metode yang digunakan adalah metode campuran di mana pendekatan kuantitatif dilakukan untuk menganalisis persepsi masyarakat dan wisatawan terkait dengan kawasan pengembangan, sedangkan pendekatan kualitatif digunakan dalam menganalisis kepariwisataan terkait dengan elemen pengembangan kawasan pariwisata riverfront. Teknik pengumpulan data yang dilakukan terdiri dari kuesioner pada kedua pihak, observasi lapangan, dan wawancara dengan stakeholder terkait. Berdasarkan analisis yang dilakukan, kedua kelurahan telah memiliki elemen-elemen tersebut dan dapat menjadi awal mula pengembangan kawasan pariwisata riverfront di Kota Pekanbaru, namun masih memerlukan strategi pengembangan sebagai sebuah destinasi wisata baru. Rekomendasi pengembangan yang disarankan terdiri dari strategi pengembangan destinasi meliputi pengembangan daya tarik wisata, fasilitas kepariwisataan, aksesibilitas pariwisata, dan pemberdayaan masyarakat melalui pariwisata, serta strategi pengembangan tambahan meliputi pengembangan promosi dan organisasi kepariwisataan. Kata kunci: elemen pengembangan, pariwisata, riverfront, Sungai Siak.